Asuhan Keperawatan Medikal Bedah Pada Pasien Dengan Anemia Di Ruang Rawat Inap RSUP Dr. M. Djamil Padang - Asti Aisyah; Hilma Yessi; Linda Marni; Debby Silvia Dewi (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Anemia is a condition characterized by decreased hemoglobin levels in the body. According to the World Health Organization (WHO), approximately 191 million adolescent girls worldwide suffer from anemia. West Sumatra Province had an anemia prevalence rate of 29.8% in 2024, the highest among provinces on Sumatra Island. At RSUP Dr. M. Djamil Padang, anemia ranked first with 3,073 reported cases. This study aimed to implement nursing care directly for patients with anemia through the nursing process approach. The study used a case study method with data collection techniques including interviews, observations, physical examinations, and documentation studies. The nursing diagnoses identified were ineffective peripheral perfusion, nutritional deficit, sleep pattern disturbance, and activity intolerance. After nursing interventions were implemented, the patient’s condition improved, indicated by an increase in hemoglobin level to 11.1 g/dL, blood pressure of 128/80 mmHg, oxygen saturation increasing to 96%, and improved appetite and activity tolerance. Patients are expected to maintain a healthy lifestyle, consume iron-rich foods, and attend regular health check-ups to monitor recovery progress.